Pengembangan Sistem Pendaftaran dan Pengelolahan Laporan Magang di Kominfo Kota Palembang Berbasis Website Menggunakan Next Js dan Express - Muhammad Samsu Hidayattullah; Muhammad Izman Herdiansyah; Heri Suroyo; Ade Putra (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to develop a web-based information system for internship registration and report management at the Palembang City Communication and Informatics Office. Previous studies have developed internship information systems that generally focus on online registration, document submission, certificate generation, academic administration, and notification features. However, existing systems typically do not include secure account verification, structured daily logbook monitoring, or integrated role-based data management tailored for government institutions. These limitations create a gap that this study addresses by developing a more comprehensive and transparent internship management solution. A descriptive qualitative approach was used through interviews and observations, and a prototyping model guided the system development process. The system was built using Next.js, Express.js, MongoDB, JSON Web Token (JWT), Nodemailer, and Tailwind CSS, with features such as online registration, document upload, account verification, daily logbook submission, final report upload, and role-based access for admins and supervisors. Implementation results show improvements in administrative speed, communication, data accuracy, and transparency compared to manual processes. Overall, the system supports a more modern, efficient, and structured internship management process within government institutions.